Comparative Analysis Between Scarfskin and Scarcocarp of Citrus medica L. var. sarcodactylis Swingle by HPLC Fingerprints and Multi-components Content Determination - Hualing LUO; Haixia LIN; Minfeng ZHU; Lijuan YANG; Xia WANG (Shipin gongye ke-ji, 2023)
Objective: The scarfskin and scarcocarp of 16 batches of Citrus medica L. var. sarcodactylis Swingle were collected as the research objects to find out the differences between scarfskin and scarcocarp. Methods: The fingerprints of scarfskin and scarcocarp of Citrus medica L. var. sarcodactylis Swingle were established by HPLC, and the content of multicomponents was determined respectively. Result: Eight common peaks were picked up in scarcocarp, 18 in scarfskin, and six constituents were identified as scopoletin, scoparone, hesperidin, diosimin, 5,7-dimethoxy coumarin and bergapten. The similarity evaluation system for chromatographic fingerprint of traditional Chinese medicine was employed for similarity analysis. The scarfskin and scarcocarp of Citrus medica L. var. sarcodactylis Swingle in Leshan City had good similarity with their respective reference fingerprints, both greater than 0.90. The similarity between the scarfskin and scarcocarp of the same batch of Citrus medica L. var. sarcodactylis Swingle was very low, only 0.10 to 0.35. On this basis, the contents of six identified components were determined. In the scarfskin of Citrus medica L. var. sarcodactylis Swingle six components were detected, and the contents of 5,7-dimethoxy coumarin and diosimin were higher. But the contents of hesperidin and diosimin in the scarcocarp were higher, and the other four components were not detected. Conclusion: Through HPLC fingerprint and quantitative analysis of multiple components, it was found that there were significant differences in composition and content between scarfskin and scarcocarp. With these characteristics, the scarfskin and scarcocarp of Citrus medica L. var. sarcodactylis Swingle could be used in different fields to maximize the use of resources. At the same time, the established method could be used for quality control of Citrus medica L. var. sarcodactylis Swingle, and would provide technical support for rational and efficient development and utilization of Citrus medica L. var. sarcodactylis Swingle resources.